Microwave-assisted synthesis, characterization and photoluminescence interaction studies of undoped, Zr2+, Rh3+ and Pd2+ doped ZnS quantum dots. (June 2018) - Ayodhya, Dasari; Veerabhadram, Guttena
Graphical abstract: Abstract: Here, we report the simple and low-cost synthesis of undoped, Zr 2+, Rh 3+ and Pd 2+ doped ZnS quantum dots (QDs) by a microwave-assisted method. We study the compositional, structural, and optical properties by XRD, SEM-EDX, TEM, FTIR, UV–vis and PL spectroscopy. The quantum confinement effect of the products was confirmed by means of spectroscopic measurements. XRD and TEM show that the synthesized ZnS quantum dots have cubic structures with a diameter of about less than 10 nm. The fluorescence interaction studies suggest that L-Cysteine was effectively quenched the fluorescence intensity of ZnS QDs and form stable Cys-ZnS complex using fluorescence spectroscopy.